2016
DOI: 10.1111/cxo.12329
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of reliability and repeatability of corneal curvature assessment with six keratometers

Abstract: Background Keratometric methodology varies between instruments and the differences may have a clinical impact. We investigated the agreement and reproducibility of six keratometers. Methods Keratometry was performed on 100 subjects at two separate sessions with IOLMaster 500, Pentacam, OPD scanner, Medmont E300, Javal‐Schiøtz and TMS‐5. A second observer assessed 30 subjects to determine inter‐observer variability. A single individual was assessed on 10 separate sessions to determine intra‐observer variability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 27 publications
3
24
0
1
Order By: Relevance
“…e reproducibility of the keratometric values was confirmed in the previous studies [7][8][9]. Corneal thickness was also measured using the TMS-5.…”
Section: Outcome Measuressupporting
confidence: 61%
“…e reproducibility of the keratometric values was confirmed in the previous studies [7][8][9]. Corneal thickness was also measured using the TMS-5.…”
Section: Outcome Measuressupporting
confidence: 61%
“…Another group recently found a difference of -0.033 mm (equal to 0.19 D), also regarding the steep meridian [8]. Studies based on the former version of Pentacam or Pentacam HR also indicated differences in keratometric measurements [19][20][21][22][23][24]. Karunaratne found statistically significant differences between the mean keratometric values of the IOL Master and Pentacam equivalent keratometry readings at 2-, 3-and 4.5-mm zone measurements.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that the thickness profile provided by the Pentacam and the BAD software can detect early keratoconus with a sensitivity and specificity of 98% [9]. The details provided by the Pentacam are reliable because the equipment has a high level of reliability and repeatability for keratometric and pachymetric readings [21,22]. The measurement of corneal thickness is essential in the diagnosis and evaluation of multiple ocular and corneal diseases, for establishing surgical indication, and for monitoring certain pathologies.…”
Section: Discussionmentioning
confidence: 99%